Effect of merger and acquisition on performance of listed nigerian deposit money banks - Onaolapo Adekunle Rahman; Ajala Oladayo Ayorinde (Journal of Corporate Finance Management and Banking System, 2025)
This study examined the effect of assets growth on performance of Nigerian Deposit Money Banks (NDMBs) from 2006 to 2023. Secondary data on issues such as Asset Profile (AP), Capital Structure (CS), Credit Risk (CR), Liquidity Risk (LR), and Return On Equity (ROE) covering the period of study were gathered from the annual reports and accounts of the seven (7) NDMBs out of a population of 14 listed on Nigerian Exchange Group (NXG) as at December, 2023. Panel regression analysis was adopted to evaluate the effect of asset growth (a surrogate for merger and acquisition) on return on equity (a surrogate for performance) in the NDMBs. The result of panel regression analysis on the effect of asset growth on ROE in the NDMBs revealed that three (3) out of the four (4) explanatory variables were significant in explaining the variation in ROE, these are AP (ρ = 0.0015), CS (ρ = 0.0001) and LR (ρ = 0.0002). The study concluded that M&A had positive significant effect on performance of NDMBs. The study recommends that banks’ management should embrace efficient customer service delivery, aggressive deposit drive and periodic training of staff in order to achieve improved customer patronage and performance.